Uso de coix lacryma-jobi (Poaceae: Panicoideae: Andropogoneae) en el estado de Veracruz, México - MEJÍA SAULES, MA. TERESA (Anales del Instituto de Biología serie Botánica, 2009)
THE USE OF COIX LACRYMA JOBI (LAGRIMA DE SAN PEDRO) IN THE STATE OF VERACRUZ IS DESCRIBED. THUS SPECIES IS PROBABLY FROM SOUTHEAST ASIA; IN MEXICO IT IS RECORDED FROM DIFFERENT REGIONS, IN VERACRUZ, IT IS FOUND MAINLY IN TROPICAL DECIDUOS FOREST IN TROPICAL EVERGREEN FOREST AND ALONG RIVERS. THE FRUIT IS A UITRICLE ENCLOSED BY HARD, MODIFIED LEAF SHEATH: IT IS GLOBOSE, WHITE GRAY, BROWN OR EVEN PURPLE: THE FRUITS ARE USED AS BEADS IN HANDCRAFTS. THE DISTRIBUTION IN MEXICO AND THE STATE OF VERACRUZ IS SHOWN. THE RESULT INDICATE THAT THE FRUITS ARE USED IN PRODUCING ROSARIES, NECLACES, BRACELETS, LAMPS AND CURTAINS. THERE IS NOT EVIDENCE OF CULTIVATION OF COIX LACRYMA-JOBI IN THE STATE OF VERACRUZ.